Implementasi Strategi Komunikasi Organisasi dalam Meningkatkan Motivasi Kerja: Studi Kasus PT Pallawa Sejahtera Mandiri di Kab. Mamuju - Setiawan, Muhammad Aras; Ferdiansyah, Rahmat; Sukmarini, Andi Vita (VISA: Journal of Vision and Ideas, 2024)
This study aims to determine the Implementation of Organisational Communication in Improving Work Motivation at PT Pallawa Sejahtera Mandiri in Mamuju Regency and maintain the effectiveness of organisational communication in improving employee work motivation at PT Pallawa Sejahtera Mandiri.To fulfil these objectives, qualitative research was conducted at PT Pallawa Sejahtera Mandiri in Mamuju Regency, located at Jl. Lingkar Jalur Dua Airport, Kel Sinyonyoi, Kec Kalukku, Kab Mamuju. Research data were collected through observation and in-depth interviews. The data findings were then analysed, in order to achieve the desired results. The results of this study are to determine the Implementation of Organisational Communication in Improving Work Motivation at PT Pallawa Sejahtera Mandiri in Mamuju Regency in this study, PT Pallawa Sejahtera Mandiri includes various factors both internal and external, such as providing salaries/incentives, appreciation for performance, opportunities to take part in education and training, a comfortable work environment, and adequate office facilities. In increasing employee motivation in the office, it is determined by several things, including openness in communication, good human resource management, solid cooperation with all members of the organisation, and a clear understanding of the duties and functions of each employee in their field.